REMEDIASI MISKONSEPSI SISWA MENGGUNAKAN MODEL APTITUDE TREATMENT INTERACTION (ATI) PADA MATERI TEKANAN HIDROSTATIS DI SMP - Siti Maimunah; Edy Tandililing; Syukran Mursyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aimed to find out the effectiveness of the application of Aptitude Treatment Interaction (ATI) in reduce the number of student’s misconception of hydrostatic pressure at Junior High School 22 Pontianak. This research used pre-experiment dsign form used one group pretest-posttest design. The population is the entire class of IX in Junior High School 22 Pontianak.ThisReseach used intact group which the outcome is class of IX D with 27 student. The instrument of this research is diagnostic test consist of 9 multiple choicewith open reasons. The percentage of student’s misconception decreasing is 82% after the remediation with ATI models on hydrostatic pressure. McNemar test with the 5% significant point showed that there is a significant change of the student’s conception after being given remediation activity using the models. The effect size of ATI models in the remediation of misconception is 0,638 with a high-category. So the ATI models is effective to reduce the number of student’s misconception. Keywords: Aptitude Treatment Interaction, ATI, remediation, misconception, hydrostatic pressure.